1988
DOI: 10.1007/bf00027383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and analysis of four potato tuber mRNAs

Abstract: Tuberization in potato is a complex developmental process involving the expression of a specific set of genes leading to the synthesis of tuber proteins. We here report the cloning and analysis of mRNAs encoding tuber proteins. From a potato tuber cDNA library four different recombinants were isolated which hybridized predominantly with tuber mRNAs. Northern blot hybridization experiments showed that three of them, pPATB2, p303 and p340, can be regarded as tuber-specific while the fourth, p322, hybridizes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
178
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(181 citation statements)
references
References 51 publications
(73 reference statements)
3
178
0
Order By: Relevance
“…In addition to DNA sequence information, the presence of suitable Asel and Taql sites in the coding region of the gene was a prerequisite. The patatin B2 gene (STPATB2, EMBL Data Library accession number X13178; Stiekema et al, 1988) was found to fulfil these criteria. The TDF was predicted to yield a fragment of 570 bp when selective base exten- sions AA (Asel-end) and AC (Taql-end) were used on the 3' ends of the primers.…”
Section: Analysis Of Gene Expression Using Cdna-aflp and Northern Anamentioning
confidence: 99%
“…In addition to DNA sequence information, the presence of suitable Asel and Taql sites in the coding region of the gene was a prerequisite. The patatin B2 gene (STPATB2, EMBL Data Library accession number X13178; Stiekema et al, 1988) was found to fulfil these criteria. The TDF was predicted to yield a fragment of 570 bp when selective base exten- sions AA (Asel-end) and AC (Taql-end) were used on the 3' ends of the primers.…”
Section: Analysis Of Gene Expression Using Cdna-aflp and Northern Anamentioning
confidence: 99%
“…Plant defensins have initially been identified in seeds , and recently been reported in other plant organs and tissues, e.g., leaves, flower, fruit, pods and tubers (Stiekema et al 1988;Chiang and Hadwiger 1991;Meyer et al 1996;Urdangarin et al 2000). They play a significant role in host defense.…”
Section: Introductionmentioning
confidence: 99%
“…cDNA probes were prepared from total RNA isolated from vegetative mycelium and knobs, grown under identical conditions to those used in the construction of the cDNA libraries. Total RNA was extracted according to Stiekema et al (1988) and purified further on an RNeasy plant mini kit spin column (Qiagen). To obtain the required amounts of RNA from limited amounts of starting material, two rounds of antisense RNA (aRNA) amplification were performed using the MessageAmp kit (Ambion).…”
Section: Methodsmentioning
confidence: 99%